Integrating Generative AI in Energy-Efficient Smart Homes to Foster STEM and Technology Literacy in Early Childhood - Budinugraha, Deva Alvyn; Andayani, Wuwuh (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
The advancement of generative artificial intelligence (AI) has opened new opportunities to support early childhood learning through smart home environments. This study aims to explore the integration of generative AI in energy-efficient smart homes as a medium for STEM (Science, Technology, Engineering, Mathematics) education and the enhancement of technology literacy in early childhood. Through automation features such as lighting control, room temperature regulation, and electricity consumption monitoring, children are introduced to energy concepts in a contextual manner while interacting directly with virtual assistants that can explain, respond to questions, and provide learning simulations tailored to their developmental level. A qualitative, literature-based approach is used to examine how this interaction can create interactive, adaptive, and enjoyable learning experiences. The findings suggest that AI-powered smart homes can serve as alternative learning environments that practically introduce young children to STEM concepts while also fostering energy awareness and responsible use of technology from an early age. With appropriate parental guidance, this system has the potential to become a humanistic educational tool aligned with the developmental needs of early childhood learners.